To your eternity. 15 - Ōima, Yoshitoki (Kodansha Comics, an imprint of Kodansha USA Publishing, LLC, 2021)
"In a world lurking with enemies long assumed to be defeated, Fushi must grapple with parasitic Nokkers parading as beloved neighbors, mothers, and siblings. Before long, the Beholder appears before Fushi as a young boy, bringing word of the Nokkers' devastating victory . . ."--